The Role of Law in Addressing Overpopulation Problems in Big Cities, A Case Study of Policy and Its Implementation in Bali in 2010-2019: Study Literature Review - Daniel Dewantoro Rumani; Upik Mutiara; Abdul Karim; Erlin Veronica Hartanto (Greenation International Journal of Law and Social Sciences, 2024)
The increasing population has caused various problems, such as severe traffic congestion to environmental degradation that threatens Bali's unique biodiversity. These problems have an impact on the quality of life of residents and the attractiveness of Bali as a tourist destination. As a result, strategic actions that focus on sustainable development, and better environmental management, According to BPS data, the population of Bali increased by 15 percent from 2010 to 2019. However, this population increase also raises problems, especially related to infrastructure, public services, and environmental preservation amidst rapid development, but studies on the effectiveness of implementation in the field are still limited. This study aims to fill this gap by analyzing in depth the factors that influence the success or failure of population control policy implementation in Bali, especially from a legal perspective. By understanding the obstacles faced, this study is expected to provide more effective policy recommendations to overcome the problem of overpopulation and achieve sustainable development in Bali.